The effects of training transfer on training program evaluation and effectiveness of training program/ Romi Rampun@Ramlan, Zuraidah Zainol and Dewi Tajuddin - Rampun@Ramlan, Romi; Zainol, Zuraidah; Tajuddin, Dewi (Faculty of Information Management, 2021)
Evaluation of training programs is an important aspect in determining the effectiveness of training programs conducted by an organization. Two dimensions of training program evaluation namely response and learning are used as variables in this study. The design of this study is in quantitative, based on the survey method. The study was conducted at the Tun Abdul Razak Library, one of the Public Institutes of Higher Learning in Malaysia. A total of 288 respondents consisting of library staff were involved in this study. Data analysis was performed using SmartPLS Software (SmartPLS-SEM) using multivariate analysis technique Structural Equation Modeling (SEM). The results of the study found that there is a significant relationship between the evaluation of training programs on the effectiveness of training programs. This study also found that training transfer acts as a mediating variable between training program evaluation and training program effectiveness. This study will be able to be used by the human resource management division in implementing the evaluation of training programs as one of the effectiveness in planning training programs.